Carbonate reservoirs : porosity and diagenesis in a sequence stratigraphic framework - Moore, Clyde H.; Wade, William J.; ScienceDirect eBooks (Amsterdam ; New York : Elsevier Science, 2013)
The 2nd Edition of Carbonate Reservoirs aims to educate graduate students and industry professionals on the complexities of porosity evolution in carbonate reservoirs. In the intervening 12 years since the first edition, there have been numerous studies of value published that need to be recognized and incorporated in the topics discussed. A chapter on the impact of global tectonics and biological evolution on the carbonate system has been added to emphasize the effects of global earth processes and the changing nature of life on earth through Phanerozoic time on all aspec.
The basic nature of carbonate sediments and sedimentation -- The application of the concepts of sequence stratigraphy to carbonate rock sequences -- The impact of global tectonics and biologic evolution on the carbonate system -- The nature and classification of carbonate porosity -- Carbonate diagenesis : introduction and tools -- Marine diagenetic environment -- Evaporative marine diagenetic environment -- Meteoric diagenetic environment -- Summary of early diagenesis and porosity modification of carbonate reservoirs in a sequence stratigraphic and climatic framework -- Burial diagenetic environment -- Natural fracturing in carbonate reservoirs -- Case histories.
Includes bibliographical references (pages 341-360) and index.
Print version record.
Elsevier
Keywords: Carbonate reservoirs; Carbonate rocks -- Permeability; Diagenesis; Porosity; Sequence stratigraphy; NATURE -- Rocks & Minerals; Electronic books